Behaviour and design of beam-to-column connections under fire conditions - Ramli Sulong, N.H.; Elghazouli, A.Y.; Izzuddin, B.A. (Elsevier, 2007)
In this paper, the main approaches used for developing a component-based connection model are presented and discussed. The model is capable of simulating the behaviour of typical connection configurations in both steel and composite framed structures under monotonic and cyclic loading conditions at ambient as well as elevated temperatures. Validation of the proposed connection model is carried out by comparison against a range of available experimental results, and implementation is undertaken within an advanced finite element program that accounts for material and geometric non-linearities. A series of sensitivity studies are then presented in order to demonstrate the scope of application of the proposed model, and to examine the influence of connection behaviour on the overall structural performance in fire. A number of structural configurations are investigated starting from isolated members and reaching more detailed representations. Several factors are assessed including connection type, boundary conditions and temperature effects. Finally, key parameters and considerations related to connection design are examined.